Palmyre-Tadmor : une histoire politique et sociale des ruines - Laurence Gillot (Les Cahiers d’EMAM)
The study of the “heritagization” of the ruins and the archaeological site of Palmyra allows us to understand the evolution of views and uses, both political and social, of the remains of this ancient caravan city, which has become a place of memory, both national and global, as well as a major heritage and tourist site in Syria. Palmyra is also an object of desire and a place of conflict where the recent destruction by Daesh and the subsequent debates on its reconstruction have also reminded us of the importance of the ideological and economic issues associated with this site. Furthermore, these processes were marked by the commitment of various actors: travelers, archaeologists, foreign and national institutions, associations, local populations, thus contributed to the recognition and transmission of a heritage that was sometimes shared, sometimes contested. This article thus discusses how the development of Palmyra as heritage took place over a long period of time, and was marked by movements of construction/deconstruction, forgetting-abandonment/rediscovery-reuse.